Powering Up Productivity in Rural Lao PDR : Stimulating Small and Medium Enterprises to Use Electricity for Income Generation - Tuntivate, Voravate Tig (World Bank, Washington, DC, 2013)
This study s broad goal was to identify opportunities for promoting productive uses of electricity in existing as well as among new small and medium enterprises (SMEs) in the rural villages of Lao PDR to generate income for rural people and promote economic development. To this end, the study team conducted a market analysis of current businesses and services, as well as major agro-processing and other income-generating activities in (i) six selected central and southern provinces connected to grid-based electricity and (ii) 10 rural villages of a remote northern district that rely on renewable energy based, off-grid power supply. Based on the survey results, the study team identified opportunities for the SMEs to switch to or adopt electricity for productive purposes; major obstacles faced by the SME owners in utilizing electricity more fully; and suggested ways to overcome these barriers, including the facilitating role of EdL (Electricité du Laos, the country s national utility company. This study relied on a social marketing survey conducted in February 2011 as the primary data source. It also drew from literature reviews and information gathered from government agencies and international organizations. Three sets of field surveys were conducted. The first set focused on rural villages with access to grid electricity whose main crop is rice; the surveys covered three central (Bolikhamxai, Khammouan, and Savannakhet) and three southern (Salavan, Champasak, and Attapue) provinces. The second set focused on rural villages with access to grid electricity whose main crop is coffee; the surveys covered the same three southern provinces (Salavan, Champasak, and Attapue). Finally, the third set focused on 10 rural villages in the Muang Mai district of Phongsaly province (Sobnaon, Houayvangkao, Nakang, Houaychik, Naxong, Sobhoun, NamNga, Xongneua, Sensaat, Nakham), which are served by an isolated grid system